2021
DOI: 10.1021/acsenergylett.1c00364
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Boundary Layer Simulation of Pulsed CO2 Electrolysis on a Copper Catalyst

Abstract: Pulsed electrolysis has been demonstrated to improve the faradaic efficiency (FE) to C 2+ products during the electrochemical reduction of CO 2 over a Cu catalyst, but the nature of this enhancement is poorly understood. Herein, we developed a timedependent continuum model of pulsed CO 2 electrolysis on Cu in 0.1 M CsHCO 3 that faithfully represents the experimentally observed effects of pulsed electrolysis. This work shows that pulsing results in dynamic changes in the pH and CO 2 concentration near the Cu su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
123
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(131 citation statements)
references
References 40 publications
3
123
0
5
Order By: Relevance
“…This rate order is consistent with the linear trends observed in Fig. 2e and is consistent with previous experimental studies of CO reduction (COR) 9,12,26,30,34 . However, recent studies of vapour-phase COR have demonstrated that appreciable θ *CO can be achieved in porous catalyst layers, causing the rate order with respect to CO concentration to decrease as the partial pressure increases, a behaviour captured by a Langmuir adsorption model (Supplementary Fig.…”
Section: Simulation Of Co Mass Transport and Adsorption In An S-gdesupporting
confidence: 93%
See 1 more Smart Citation
“…This rate order is consistent with the linear trends observed in Fig. 2e and is consistent with previous experimental studies of CO reduction (COR) 9,12,26,30,34 . However, recent studies of vapour-phase COR have demonstrated that appreciable θ *CO can be achieved in porous catalyst layers, causing the rate order with respect to CO concentration to decrease as the partial pressure increases, a behaviour captured by a Langmuir adsorption model (Supplementary Fig.…”
Section: Simulation Of Co Mass Transport and Adsorption In An S-gdesupporting
confidence: 93%
“…A two-dimensional (2D) continuum model of the cathodic chamber of the cell was developed to rationalize and guide the results and design, respectively. Multiple previous studies in aqueous electrolytes have shown that the generation of C 2+ products from CO follows an approximately first-order rate dependence on CO concentration at low CO partial pressures, for which the fraction of empty Cu sites is near unity 2,9,26,[34][35][36][37][38] . This rate order is consistent with the linear trends observed in Fig.…”
Section: Simulation Of Co Mass Transport and Adsorption In An S-gdementioning
confidence: 93%
“…The higher local pH and CO accumulation were thus achieved, benefiting to C 2+ production and HER suppression. [43,190,191] The net effect of alternating cathodic potentials also helps accumulate CO 2 in electrode surface to enhance carbon compounds production over HER. [45] In addition to CO 2 RR activity and selectivity, pulsed electrolysis further shows its availability to improve the stability of gas diffusion electrode (GDE)-based CO 2 RR electrolyzer.…”
Section: Pulsed Electrolysis: a Promising Technique To Manipulate The...mentioning
confidence: 99%
“…The higher local pH and CO accumulation were thus achieved, benefiting to C 2+ production and HER suppression. [ 43,190,191 ] The net effect of alternating cathodic potentials also helps accumulate CO 2 in electrode surface to enhance carbon compounds production over HER. [ 45 ]…”
Section: Pulsed Electrolysis: a Promising Technique To Manipulate The...mentioning
confidence: 99%
“…Despite decades of research efforts, Cu remains the only catalyst capable of producing significant amounts of C 2+ products, containing more than one carbon atom . In doing so, however, Cu also produces a medley of other products of varying economic value, presenting a challenge for industrial viability in the absence of a carbon tax or credit. , Several strategies for improving the Faradaic efficiency of Cu toward C 2+ products have emerged, including engineering of the electrode assembly and electrolyte, dynamic potential control, and surface roughening. In this contribution, we examine opportunities and intrinsic limitations in tuning catalytic selectivity of copper via surface structure engineering.…”
mentioning
confidence: 99%